KARAKTERISTIK PERSONAL AUDITOR SEBAGAI ANTESEDEN PERILAKU DISFUNGSIONAL AUDITOR DAN PENGARUHNYA TERHADAP KUALITAS HASIL AUDIT - Fatimah, Annisa (JURNAL MANAJEMEN DAN AKUNTANSI, 2012)
Abstract: The aim of this research to examine: 1) do the auditor personal character include of locus of control, turnover intention, and self rate performance influence the dysfunctional behavior, and 2) do the dysfunctional behavior influence the audit quality.The sampling method of this research is purpossive sampling so that 281 auditors were choose and 86 datas can be used to analyze. Through quetionnare that measured by likert scale, this research use Path Analysis to examine all of that variables.  The result of this research showed that all of the independent variables influence the dysfunctional behavior so that increasing of locus of control, turnover intention, and self rate employee performance can make dysfunctional behavior increase.  On the contrary, decreasing of locus of control, turnover intention, and self rate employee performance can make dysfunctional behavior decrease too. Key words: auditor personal characteristic, audit quality.